NOVELTIES IN BRAZILIAN BEGONIACEAE VI: Taxonomic notes - Kollmann, Ludovic Jean Charles (Phytotaxa, 2023)
As a result of a taxonomic study on Begoniaceae from Brazil, eight taxa are lectotypified. Lectotypes of Begonia bahiensis, B. coccinea, B. echinosepala, B. herbacea var. ellipticifolia, B. juliana, B. leptotricha, B. metallica and B. saxifraga are designated. Begonia attenuata var. herbacea, B. bonitoensis var. intermedia, B. cantareira, B. costello and B. fruticosa var. robusta are confirmed as invalid names.